2019
DOI: 10.1038/s41422-019-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium oligomannate therapeutically remodels gut microbiota and suppresses gut bacterial amino acids-shaped neuroinflammation to inhibit Alzheimer’s disease progression

Abstract: Recently, increasing evidence has suggested the association between gut dysbiosis and Alzheimer's disease (AD) progression, yet the role of gut microbiota in AD pathogenesis remains obscure. Herein, we provide a potential mechanistic link between gut microbiota dysbiosis and neuroinflammation in AD progression. Using AD mouse models, we discovered that, during AD progression, the alteration of gut microbiota composition leads to the peripheral accumulation of phenylalanine and isoleucine, which stimulates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
561
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 809 publications
(653 citation statements)
references
References 61 publications
(70 reference statements)
14
561
1
8
Order By: Relevance
“…A recent investigation has shown that GV-971, a sodium oligomannate, produced an evident and consistent improvement of cognition in phase 3 clinical trial in China. GV-971(degree of polymerization: 2-10, molecular weight: up to 1kDa, quantities ingested: 100 mg/kg/day, oral administration) suppressed gut dysbiosis and the associated phenylalanine/isoleucine accumulation, harnessed neuroinflammation, and reversed the cognition impairment in mild-to-moderate AD patients [103]. All these findings offered the possibility of a conceptual advancement in the understanding of the etiology of AD.…”
Section: Neuroprotective Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…A recent investigation has shown that GV-971, a sodium oligomannate, produced an evident and consistent improvement of cognition in phase 3 clinical trial in China. GV-971(degree of polymerization: 2-10, molecular weight: up to 1kDa, quantities ingested: 100 mg/kg/day, oral administration) suppressed gut dysbiosis and the associated phenylalanine/isoleucine accumulation, harnessed neuroinflammation, and reversed the cognition impairment in mild-to-moderate AD patients [103]. All these findings offered the possibility of a conceptual advancement in the understanding of the etiology of AD.…”
Section: Neuroprotective Activitymentioning
confidence: 91%
“…Future studies identifying the crucial strains of bacteria accounting for the effects of pM on metabolic and neuroinflammation changes will be critical. In addition, extensive research will be required to identify other mechanistic links connecting gut microbiota and neuroinflammation [20,103], and uncover other possible effects of AOS on intestinal microbes.…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…The identified protein lists were generated with a target-decoy strategy based on a FDR cut-off of 0.01. Label-free quantification (LFQ) intensity of proteins across all samples were obtained with the MaxLFQ algorithm 17 . Taxonomic and functional enrichment analysis was performed using the enrichment module on iMetalab.ca 40 through inputting the list of altered proteins groups.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have added drug stimulation to the in vitro gut bacteria at various points during the growth phases of the gut microbiome. For example, Maier et al 16 , Li et al 15 and Wang et al 17 studied microbial responses to drugs by inoculating bacterial strains or fecal inoculum into culture mediums containing drugs. Wu et al 10 used the SHRIM to explore the effect of metformin on a stabilized gut microbial community in vitro, and added the metformin after one week of stabilization in SHRIM.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are now convinced that gut bacteria may be involved in many neurological disorders including AD. The oligomannate discovery opens the door widely to address many other diseases via targeting the microbiome [15].…”
Section: Highlighted By Rafik Karamanmentioning
confidence: 99%